2020
DOI: 10.1101/2020.09.09.289199
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Water Source Use, Quality of Water, Sanitation and Hygiene Perceptions among Urban Households in North-West Ethiopia: A Cross-Sectional Study

Abstract: BackgroundClean water is an essential element for human health, wellbeing, and prosperity. Every human being has the right to access safe drinking water. But, in now day, due to rapid population growth, illiteracy, lack of sustainable development, and climate change; it still faces a global challenge for about one billion people in the developing nation. The discontinuity of drinking water supply puts in force households either to use unsafe water storage materials or to use water from unimproved sources. This… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 24 publications
3
8
1
Order By: Relevance
“…The findings of some studies in Ethiopia and Ghana are consistent with the current one [21,23,28]. They indicated that households headed by older people were more likely to have access to improved water and sanitation facilities [21,23,28]. In contrast, in Eswatini, the age of the household head was negatively associated with the use of water from an improved source [27].…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The findings of some studies in Ethiopia and Ghana are consistent with the current one [21,23,28]. They indicated that households headed by older people were more likely to have access to improved water and sanitation facilities [21,23,28]. In contrast, in Eswatini, the age of the household head was negatively associated with the use of water from an improved source [27].…”
Section: Discussionmentioning
confidence: 52%
“…Also, some authors suggest that as people age, they make choices or adopt behaviours that improve their quality of life [23]. The findings of some studies in Ethiopia and Ghana are consistent with the current one [21,23,28]. They indicated that households headed by older people were more likely to have access to improved water and sanitation facilities [21,23,28].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Marriage increases the family size and larger families require more water and could have made a better effort to own tap water. Similarly, Gebremichael et al [30] reported a significant association of households' drinking water sources with age, educational status, and family size in northwest Ethiopia. Earlier, Fortune and Sikod [31] indicated a significant association of distance of water sources and household size with the choice of drinking water source in Cameroon.…”
Section: Discussionmentioning
confidence: 93%